2007
DOI: 10.1093/geront/47.5.633
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship Among Hearing Impairment, Linguistic Communication, Mood, and Social Engagement of Residents in Complex Continuing-Care Facilities

Abstract: Purpose. The purpose of this work was to examine how structural factors, residents' needs for physical and psychosocial assistance, and the work stressors experienced by employees are related to the quality of life of elderly residents in long-term care. Design and Methods. Cross-sectional survey data were collected from 1,194 employees and 1,079 relatives of residents in 107 residential-home units and healthcenter bed wards. Data were analyzed using multilevel modeling. Results. The majority of differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 66 publications
(69 reference statements)
1
41
0
1
Order By: Relevance
“…Alguns autores acreditam que o processo de debilidade sensorial, que se dá com o passar dos anos, seja normal e inerente a todos os seres humanos, percebido em menor ou maior grau pelos diferentes indivíduos 17 , enquanto outros o caracterizam como uma morbidade e recomendam sua pesquisa e intervenção adequada 18 .…”
Section: Discussionunclassified
“…Alguns autores acreditam que o processo de debilidade sensorial, que se dá com o passar dos anos, seja normal e inerente a todos os seres humanos, percebido em menor ou maior grau pelos diferentes indivíduos 17 , enquanto outros o caracterizam como uma morbidade e recomendam sua pesquisa e intervenção adequada 18 .…”
Section: Discussionunclassified
“…The problem gets more intricate when adding spectral smearing on impaired ears (Plomp, 1978), which makes listening even more laborious (Hicks et al, 2002). There will also be a reduction in the number of interpersonal communications (Clark et al, 1999), which increases the handicap (WHO, 2000) in a way that is similar to the consequences of hearing loss (Brink et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Good hearing is a prerequisite for verbal communication and thus essential for social 24 interaction with other people (Brink & Stones, 2007). However, hearing problems are extremely 25 common in older adults.…”
mentioning
confidence: 99%
“…It has also been shown that even mild cognitive impairment has a deleterious 342 effect on auditory processing (Rahman et al, 2011), which in turn may hamper verbal 343 communication. According to Brink et al, impaired verbal communication is a factor that 344 mediates the influence of hearing loss on social engagement (Brink & Stones, 2007). Further, 345 cognitive problems may disturb verbal communication due to the misinterpretations of 346 nonliteral meanings used in spoken language (Maki, Yamaguchi, Koeda, & Yamaguchi, 2013).…”
mentioning
confidence: 99%